Aboveground productivity and community stability tend to keep stable under long-term fencing and nitrogen fertilization on restoration of degraded grassland. (July 2022) - Sheng, Jun; Zhou, Meng; Guo, Yumeng; Yuan, Yujia; Li, Xin; Zhang, Wen-Hao; Bai, Wenming
Highlights: Using community productivity and stability to estimate restoration of degraded steppe. Community productivity did not continuously increase as restoration duration extended. Degraded steppe reached optimal status after seven years' restoration. Community stability decreased in early phase, but maintained stable in later phase. Species asynchrony and dominant species stability regulated community stability. Abstract: Restoration of degraded grassland is an essential issue which has been widely concerned but not effectively resolved. Fencing and nitrogen fertilization are common and efficient restoration practices. However, there are still controversy on the effectiveness and duration of fencing and nitrogen fertilization on the restoration of degraded grassland. To estimate the effects of fencing and nitrogen fertilization on the community above-ground net primary productivity (ANPP) and stability, and explore the underlying mechanism, an 18-year (from 2003 to 2020) fencing and nitrogen fertilization (8 g N m −2 year −1 ) field experiment was conducted on a degraded temperate steppe in Inner Mongolia. Community ANPP and species richness were measured at the peak of plant biomass in growing season (mid-August) from 2004 to 2020. Temporal stability of community ANPP were calculated to estimate the community stability under different restoration managements. We found that both fencing and nitrogen fertilization can significantly increase the ANPP. Nevertheless, ANPP tended to keep stable rather than continuously increase with the extension of restoration duration. Long-term fencing and nitrogen fertilization significantly reduced the stability of ANPP in early stage of restoration (2004–2010), but had no significant effect on the stability of ANPP in later stage (2011–2020). Moreover, the stability of ANPP maintained stable with extension of restoration duration. Furthermore, we found that the biological factors that regulate the community stability were similar between the two restoration measures. Specifically, the stability of ANPP was regulated by species asynchrony in early phase, while, it was mediated by both species asynchrony and dominant species stability in later phase. Overall, from the perspective of community ANPP, the degraded steppe reached optimal status after approximately seven years of fencing and nitrogen fertilization, appropriate utilization after seven years' restoration may be conducive to maintain ANPP and the stability of ANPP. This study provided valuable information for better restoring and managing the degraded temperate steppes.